Prevalence and impact of SARS-CoV-2 infection among patients with acute ischaemic stroke: a nationwide register-based cohort study in Denmark - Søren Paaske Johnsen; Claus Ziegler Simonsen; Grethe Andersen; Rolf Ankerlund Blauenfeldt; Janne Kaergaard Mortensen; Jakob Nebeling Hedegaard; Christian Morberg Wejse (BMJ Open)
Objectives An increased risk of stroke has been reported among patients with COVID-19 caused by SARS-CoV-2. We aimed to investigate the nationwide prevalence of SARS-CoV-2 among patients with acute ischaemic stroke and to study the impact on stroke severity, quality of care and mortality on an individual patient level.Design This was a nationwide register-based cohort study.Setting We used data from several Danish registers which were linked at an individual patient level using the unique civil registration number assigned to all Danish citizens. Patients were identified from the Danish Stroke Registry and information on SARS-CoV-2 infection status was collected from the Danish National COVID-19 Registry. Concurrent SARS-CoV-2 infection was defined as a positive PCR test within 31 days prior to, and 1 day after, stroke admission. Information on comorbidity was collected from the Danish National Patient Registry and information on vital status was collected from the Danish Civil Registration System.Participants A total of 11 502 patients admitted with acute ischaemic stroke from 10 March 2020 to 31 May 2021 were included in the study.Results Among the included patients, the majority (84.6%) were tested for SARS-CoV-2, but only 68 had a positive test. These patients were more prone to have atrial fibrillation and were more often treated with reperfusion therapy. They had a significantly increased risk of severe stroke (adjusted relative risk (aRR) 1.93, 95% CI: 1.22 to 3.04) and a significantly increased 30-day mortality risk (aRR 2.29, 95% CI: 1.19 to 4.39). There was no difference in the proportion of patients fulfilling relevant performance measures on quality of care.Conclusion In this nationwide study, only 0.6% of patients with acute ischaemic stroke were tested positive for a concurrent SARS-CoV-2 infection. The patients with SARS-CoV-2 presented with more severe strokes.